Structural equation model For the relationship between accounting information system and internal audit effectiveness with moderating effect of experience - Khalid, Azam Abdelhakeem (Tanjong Malim, 2019)
Structural equation model For the relationship between accounting information system and internal audit effectiveness with moderating effect of experience by Khalid, Azam Abdelhakeem